TINJAUAN HUKUM ISLAM TERHADAP PROSESI SESERAHAN DALAM PERNIKAHAN ADAT BETAWI - Syarifudin Syarifudin; M.Mujib Qalyubi; Irfan Hasanudin (Mozaic : Islam Nusantara, 2019)
This study aims to find out how the procession of surrender in traditional Betawi marriage and how a review of Islamic law against it. Is there a proposition that prohibits / forbids it or is required. This research was conducted in the area of South Kedoya Village, Kebon Jeruk District, City. West Jakarta.This research is a legal research that uses qualitative research methods with an ethnographic approach and is descriptive in nature. In extracting information, researchers use observation and interview techniques. Researchers used the snowball technique so that the information obtained could go as far as possible into Betawi cultural customs. Researchers position themselves as research instruments themselves so that the information obtained can reach its roots. The data analysis used is the Miles and Huberman model data analysis, which is interactive and continues until the data is saturated. In this study, researchers found a philosophical, sociological and ideological foundation that was embedded in the culture of Betawi marriage customary marriage. Researchers also found the arguments underlying the implementation of these surrender activities. The evidence is sourced from the Qur'an, Hadith and Ijma 'and Qiyas of the scholars'. This research concludes that the culture of seserah in Betawi traditional marriage has a philosophical and ideological foundation that has been firmly embedded in the Betawi community in the South Kedoya region. So that this surrender event becomes mandatory for people who want to marry Betawi people. whereas according to Islamic law, basically customary law is mubah (allowed). But it can become mandatory